Automated perfusion calculations vs. visual scoring of collaterals and CBV-ASPECTS: Has the machine surpassed the eye? - Psychogios, Marios-Nikos; Sporns, Peter B.; Ospel, Johanna; Katsanos, Aristeidis H.; Kabiri, Reza; Flottmann, Fabian A.; Menon, Bijoy K.; Horn, Mackenzie; Liebeskind, David S.; Honda, Tristan; Ribo, Marc; Ruiz, Manuel Requena; et al. (Clinical neuroradiology, 2021)
Use of automated perfusion software has gained importance for imaging of stroke patients for mechanical thrombectomy (MT). We aim to compare four perfusion software packages: 1) with respect to their association with 3‑month functional outcome after successful reperfusion with MT in comparison to visual Cerebral Blood Volume - Alberta Stroke Program Early CT Score (CBV-ASPECTS) and collateral scoring and 2) with respect to their agreement in estimation of core and penumbra volume.
Online veröffentlicht: 20. November 2020
Gesehen am 22.03.2024